Le printemps de Chine, French spring - Jian, Qin; Teerlinck, Hilde; Crac Alsace, Altkirch (Altkirch : CRAC (Centre Rhenan d'Art Contemporain) Alsace Altkirch, 2004)
Tang Nan Nan ; Zhou Xiaohu ; Zen Huan Guang ; Wang Yi Ji ; Lin Xi & Fish ; Lin Lin & Jia Wen Hou ; Meiya Lin ; Rigobert, Fabien ; Mréjen, Valérie ; Huet, Elodie ; Weiss, Erich ; Ruiz de Infante, Francisco ; Bartoloméo, Joël ; Meste, Philippe ; Discrit, Julien ; Hue, Jean-Charles ; Baudy, Regis
korte biog.
Publicatie n.a.v. tentoonstelling "Le Printemps de Chine, French spring" in CRAC Alsace te Altkirch, 14.03.2004 - 23.05.2004
Engels
Frans
boek
Keywords: China; Frankrijk